(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
For many years the printers have been essential part of our offices and exposures from various printing technologies have been widely researched. The main objective of this study was to compare emitted number and mass of fine particles from laser printers and new Micro Piezo technology ink jet printers during the printing process and one hour afterwards as these emissions have potential for negative health effects.Air samples were taken with the particle size spectrometer for real-time ELPI+, Dekati (air flow rate 10 l/min). Measurements were taken 0.5 m from the printers: one hour before the test, during printing and one hour afterwards. Similar class black&white (b/w) and colour printer of each technology were tested. Each printer performed a 10-page and a 100-page test according to ECMA 328-1 Standard [1].During laser printer tests from 8324 to 19943 pt/cm3 fine particles were determined on printing phase from b/w and colour printers. Ink jet (Micro Piezo) printers produced less: from 3239 to 5247 pt/cm3. One hour after the printing phase for both types of laser printers’ there were 54722 to 152351 pt/cm3 particles in air and 4270 to 9579 pt/cm3 particles for ink jet printers. Detected particle mass differences was insignificant: in range of 0.002 to 0.012 mg/m³ for laser printers and 0.002 to 0.019 mg/m³ for ink jet printers. Micro Piezo technology printers emitted mass particles were with bigger median size μm.The highest number of particles was observed one hour after the printing for both tested printer technologies. Laser printers’ emitted 2.5 to 3.8 times more particles in printing phase and 12.8 to 15.9 times more after printing phase. Particle mass in mg/m³ was detected in the size range 6nm - 2.5 μm with no significant mass differences.